Pengembangan Ekonomi Pusat Kegiatan Belajar Masyarakat Merpati Bangsa Melalui Usaha Makanan Ringan - Frandinata, James; Renaldy, Renaldy; Gunawan, Hendry; Angel, Valencia; Geraldo H, Timothy; Faustine A., Febiani; Kuntjoro*, Antonius Puspo (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
Pusat Kegiatan Belajar Masyarakat (PKBM) is a social organization that aims as a means of community development. PKBM has various activities in it, one of which is the Business Learning Group (KBU) which is currently not running due to constraints in management. We as a group work together with PKBM in developing KBU activities so that the potential of PKBM community members can be maximized. Groups help in terms of operations, marketing, human resources, and finance. From an operational point of view focused on the snack products produced, in terms of marketing supported for consignment systems and sales with online media, in terms of human resources a management system is made so that it is organized and financially in order to record more details. This facilitator is expected to help the activities at the KBU which lead to the implementation of activities in PKBM in order to help social problems. The resulting product focuses on snacks, especially roll chips and chopsticks that do not require special abilities. HR Management is the main challenge for the group to determine the person in charge of the activities at KBU so that the business can run continuously. Making this management system in the KBU will be the main focus so that the community economy in PKBM can develop.